Dyslipidemia With Perioperative Statin Usage Is Not Associated With Poorer 24-Month Functional Outcomes After Arthroscopic Rotator Cuff Surgery. Issue 10 (August 2020) - Zeng, Gerald Joseph ShengXiang; Lee, Merrill Jian Hui; Chen, Jerry Yongqiang; Ang, Benjamin Fu Hong; Hao, Ying; Lie, Denny Tjiauw Tjoen
Background: Current literature suggests a higher rate of rotator cuff disease development in patients with dyslipidemia (DL). Moderate to high levels of DL are associated with higher rates of retear and revision surgery after arthroscopic rotator cuff repair. Statins protect against development of rotator cuff disease and mitigate the need for rotator cuff repair. Purpose: We aimed to investigate the influence of DL and statin use on postoperative functional outcomes. Study Design: Cohort study; Level of evidence, 3. Methods: Between 2010 and 2016, 266 patients underwent arthroscopic double-row rotator cuff repair for atraumatic full-thickness tears. Evaluation was conducted preoperatively and at 3, 6, 12, and 24 months postoperatively. Three functional outcome measures were used (Constant Shoulder Score [CSS], Oxford Shoulder Score [OXF], and University of California, Los Angeles, Shoulder Rating Scale [UCLASS]), as well as a visual analog scale (VAS) for pain. DL and non-DL were classified through screening of health and assessment of lipid levels within 6 months of surgery (triglycerides, total cholesterol, low-density lipoprotein, and high-density lipoprotein). Patients with DL were divided into statin users and nonusers. Types and dosages of statins were recorded, and intensity and equivalency charts were employed for standardization. Mann-Whitney U test and Pearson chi-square test were used for analysis. Generalized estimating equations and linear mixed models were used to examine the influence of DL and statin dosage, respectively on percentage change of postoperative outcome scores. Results: Increased age was associated with a higher incidence of DL ( P < .001), and 86% of the DL group was taking statins. The DL group also exhibited poorer scores preoperatively (CSS, P = .001; OXF, P = .032). No significant difference in scores was elicited between the DL and non-DL groups at 24 months. However, patients with DL experienced greater percentage improvement of CSS and OXF from preoperative baseline than did patients without DL ( P = .008 and P = .034, respectively) at 24 months. There was no significant difference in 24-month functional outcomes between statin users and nonusers. No statistically significant change of CSS; OXF; UCLASS; or VAS was noted with increasing statin doses at 24 months. Conclusion: Patients with DL with perioperative statin usage did not have poorer 24-month functional outcomes after arthroscopic rotator cuff surgery compared with those in patients without DL.